Ways еffectiveness of information culture of the future engineers and educators in the modernization of the national education system (Pedagogy of Higher and Secondary Education, 2012)
Volkova N. Ways еffectiveness of information culture of the future engineers and educators in the modernization of the national education system.In the article the way of effective information culture of the future engineers and educators in VPUZ. Proved correlative relationship between information and technological aspects of the formation of students’ information culture within the higher education informatization.
Keywords: information; information culture; future engineers; teachers